2022
DOI: 10.1038/s41467-022-35538-1
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling light absorption and carrier transport via heterogeneous doping in Ta3N5 thin film photoanode

Abstract: The trade-off between light absorption and carrier transport in semiconductor thin film photoelectrodes is a major limiting factor of their solar-to-hydrogen efficiency for photoelectrochemical water splitting. Herein, we develop a heterogeneous doping strategy that combines surface doping with bulk gradient doping to decouple light absorption and carrier transport in a thin film photoelectrode. Taking La and Mg doped Ta3N5 thin film photoanode as an example, enhanced light absorption is achieved by surface La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Ta 3 N 5 films are often reported to exhibit a broad sub-band gap absorption, <∼2.0 eV or >600 nm, attributed to defect-induced trap states. ,, Loading of Molecule 1 can be seen to slightly suppress the sub-band gap absorption, consistent with the passivation of only the surface of films (Figure a). Absorption of light within the band gap is also partially diminished upon loading of Molecule 1 , suggestive of films with a lower doping level from a reduction in the density of states near the conduction band minimum (CBM) and valence band maximum (VBM) . Characterization of the PL from neat films shows a weak near-band-edge emission at ∼2.1 eV and a strong, broad emission peak centered at ∼1.75 eV attributed to defect-induced emission (Figure b). ,, Films treated with Molecule 1 demonstrate an enhanced near-band-edge emission and the significant suppression of defect-induced emission, further supporting the efficient passivation of the films. , …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ta 3 N 5 films are often reported to exhibit a broad sub-band gap absorption, <∼2.0 eV or >600 nm, attributed to defect-induced trap states. ,, Loading of Molecule 1 can be seen to slightly suppress the sub-band gap absorption, consistent with the passivation of only the surface of films (Figure a). Absorption of light within the band gap is also partially diminished upon loading of Molecule 1 , suggestive of films with a lower doping level from a reduction in the density of states near the conduction band minimum (CBM) and valence band maximum (VBM) . Characterization of the PL from neat films shows a weak near-band-edge emission at ∼2.1 eV and a strong, broad emission peak centered at ∼1.75 eV attributed to defect-induced emission (Figure b). ,, Films treated with Molecule 1 demonstrate an enhanced near-band-edge emission and the significant suppression of defect-induced emission, further supporting the efficient passivation of the films. , …”
Section: Resultsmentioning
confidence: 97%
“…Absorption of light within the band gap is also partially diminished upon loading of Molecule 1, suggestive of films with a lower doping level from a reduction in the density of states near the conduction band minimum (CBM) and valence band maximum (VBM). 39 Characterization of the PL from neat films shows a weak nearband-edge emission at ∼2.1 eV and a strong, broad emission peak centered at ∼1.75 eV attributed to defect-induced emission (Figure 5b). 11,14,35 Films treated with Molecule 1 demonstrate an enhanced near-band-edge emission and the significant suppression of defect-induced emission, further supporting the efficient passivation of the films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In this context, hydrogen (H 2 ) is considered to be one of the most promising fuel candidates, as it can be produced by photocatalytic (PC) or photoelectrochemical (PEC) water splitting using only water and sunlight. [6][7][8] However, solar-driven PC/PEC water splitting is challenging because of its stringent thermodynamic requirements, especially for visible-light-responsive photocatalysts with narrow bandgaps. The thermodynamic requirement for PC/PEC hydrogen peroxide (H 2 O 2 ) production is less stringent because the Gibbs free energy change of oxygen reduction to produce H 2 O 2 is lower than that of water decomposition to produce H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, our group declared that a semi-transparent thin-film tantalum nitride (Ta 3 N 5 ) photoanode with CuInSe 2 solar cells facilitated STH efficiency up to 9%. 19,20 In the literature, different material and structural designs have been implemented to maximize photocurrent density up to 12.1 mA cm −2 21 and half-cell STH efficiency up to 4.07% 22 for non-transparent Ta depends on the matched photocurrent densities of the photoanode and the PV cell at an operating potential around 1.23 V versus reversible hydrogen electrode (V RHE ). Therefore, the realization of a photoanode with high current at 1.23 V RHE is imperative for the development of highly efficient solar water splitting systems like PEC-PV tandem devices.…”
mentioning
confidence: 99%
“…Wang et al revealed that dual BiVO 4 photoanodes, self-biased by illuminated PSC, improved the efficiency up to 6.5% . Recently, our group declared that a semi-transparent thin-film tantalum nitride (Ta 3 N 5 ) photoanode with CuInSe 2 solar cells facilitated STH efficiency up to 9%. , In the literature, different material and structural designs have been implemented to maximize photocurrent density up to 12.1 mA cm –2 and half-cell STH efficiency up to 4.07% for non-transparent Ta 3 N 5 photoanodes. Typically, the STH energy conversion efficiency of tandem devices depends on the matched photocurrent densities of the photoanode and the PV cell at an operating potential around 1.23 V versus reversible hydrogen electrode (V RHE ).…”
mentioning
confidence: 99%